Design and development research in instructional technology - Alias, Nor Aziah; Hashim, Sulaiman (IGI Global, 2012)
Instructional Technology (IT) research is fast moving towards innovation-based research as information and communication technology (ICT) continues to rapidly permeate the learning environments. Traditional bifurcation of quantitative and qualitative research has now been gradually blurred by dynamic approaches involving multiple techniques, solid theoretical underpinnings, extensive instructional problem analysis, well thought designs and efficient development of products or tools to offer practical solutions in order to address and resolve problems concerned with the improvement of instruction. This chapter introduces the reader to design and development research (Richey & Klein, 2007) which is theory driven, action and interventionist orientated, participant centred and collaborative. The features of this research are similarly explicated in the methodology of design experiment (Brown, 1992; Collins, 1992), development research (Van Den Akker, 1999), formative research (Reigeluth & Frick, 1999) and design based research (Bannan-Ritland, 2003). Of late, the term “educational design research” has been profusely utilized to signify this approach (Plomp & Nieveen, 2009; Van Den Akker, Gravemeijer, Mckenney & Nieveen, 2006; Vos, DeVesse & Rassul, 2006; Kelly, Lesh & Baek, 2008). Design and development research combines both pragmatic design and traditional research methods and tools such as case study, evaluation, expert reviews and interviews, allowing the appropriate method to be selected for the appropriate task and to answer specific research questions. Most importantly is the potential of design and development research to spur innovation. This chapter will act as an anchor for the rest of this book that aims to illustrate cases put forward by authors from different educational research backgrounds. The aspects of design and development research unique to each chapter are explicated as lessons learned and are expected to guide novice and proficient IT researchers.